Strategies for Economic Recovery through the Post Covid-19 Tourism and Transportation - Indriyani Indriyani; Ani Maryani (Penerbit Goodwood, 2023)
Purpose: The purpose of this research is to find a solution regarding the strategy of economic recovery through the tourism and transportation sectors. Methodology: This study uses a qualitative descriptive statistical analysis method, namely by understanding the phenomena that occurred during the covid-19 pandemic that caused the economic downturn, one of which was the tourism and transportation sectors. Results: The results of this study there are three solutions that the authors provide, among others: (1) changing the quality of service to the community; (2) improve the quality of service to the community; (3) the existence of a fiscal stimulus, namely the provision of tax incentives. Limitations: lack of references related to articles on economic sector recovery so that the results obtained are less than optimal and there is limited time in research. Contribution: as a solution for companies affected by COVID-19 regarding economic recovery strategies related to the tourism and transportation sectors.